Changing Life Patterns of Displaced Plantation Community in Vavuniya district after the independence - Selvarajan, P.; Maadhavan, M. (Sociological Association of Sri Lanka, 2009)
This research study analyses how far the life patterns of displaced plantation community has been changed after their displacement from their native place to Vavuniya district. For the purpose of this study, researchers have selected two divisions of Divisional Secretariats, Vavuniya and Vengalacheddikulam where the plantation community is highly resident. This research study is carried out through cluster sampling method and the sample consists of 100 families in 21 villages within 17 Grama Niladhari divisions. Further distribution of questionnaire and direct interviewing with the family members who are over forty years of age and married persons who were born in plantations area are considered. However, some second generation families who were born in Vavuniya also taken into consideration for analyzing the data. The first displacement took place in 1956 and the people scattered i.e. displaced to India and other districts in Sri Lanka. They had been facing various problems due to the ethnic conflict in Sri Lanka. The findings show that this community was treated as secondary people in their own land and called by different names without any rights and poorly treated by the others. But in Vavuniya their life status have been uplifted through education, ownership of land or house, better employment, voting rights, freedom to move and they all considered as Sri Lankan Tamils. Therefore the authors believe that these people have upgraded their life status in Vavuniya after the independence by the support of various government and non-government agencies continuous livelihood development activities when compare with the plantation community in the hill country.
Keywords: Plantation community; Internal displacement; Livelihood development; Life patterns